IDENTIFICATION OF COMMUNITY PERCEPTIONS OF THE SOCIO-ECONOMIC CONDITIONS OF WOMEN WORKERS IN PLANTATIONS - Delyana Rahmawany Pulungan; Tifany Zia Aznur; Dina Arfianti Saragih; Hilma Purba; Daniel Nugroho Pasaribu (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
Women workers who are called daily workers in the estate usually get a bad rating because of the type of work that is hard and not optimal in carrying out their roles in the household. However, this assessment must be correct because there are many factors that cause women to work to increase family income. This study aims to determine the perceptions of the people in Greenan Village towards women daily laborers who work for plantation companies in Greenan Village. This research is a quantitative descriptive study with a sample of 30 informants, 15 people from the community inside the estate and 15 people from outside the estate. The results show that the community has a positive and supportive perception of women (housewives) working in the estate as daily labourers, even though it looks like their work is rough, heavy and full of risks such as fertilizing, chemistry, etc. but it is known that they do it voluntarily, want to help the family economy, improve family welfare. Their husbands don't forbid them because their roles in the household as mothers and wives are not neglected. Even with work, their social interactions in the community are still good, so that the negative opinion that is usually received by women workers in the plantations is refuted.